CTLA4Ig inhibits T cell–dependent B-cell maturation in murine systemic lupus erythematosus - Mihara, Masahiko (American Society for Clinical Investigation, 2000)
Long-term administration of CTLA4Ig prevents the onset of disease in systemic lupus erythematosus–prone (SLE-prone) NZB/NZW F1 mice. To determine the mechanism of this effect, we engineered an adenovirus that expresses murine CTLA4Ig. Administration of a single high dose of this virus results in long-term expression of CTLA4Ig in the serum and absence of an immune response to the adenoviral vector. We administered Ad-CTLA4Ig to 19- to 22-week-old NZB/NZW F1 mice and evaluated the effect on anti-DNA antibody–producing B cells. We show that CTLA4Ig has a beneficial effect on murine SLE for as long as it is present in the serum. This effect is associated with decreased expansion of both the IgM and IgG autoreactive B-cell population, inhibition of immunoglobulin class switching, decreased frequency and altered pattern of somatic mutation, and a marked decrease in the numbers of activated CD4-positive T cells. In contrast, intrinsic B-cell hyperreactivity and the survival of plasma cells in the bone marrow, both of which are less dependent on T-cell help, appear to be unaffected by CTLA4Ig. High-dose CTLA4Ig did not induce permanent tolerance in this autoimmune disease model. Furthermore, although the mice survived in a conventional housing facility, treatment with Ad-CTLA4Ig was immunosuppressive.